Screen exposure and health behaviors in Saudi adults: cross-sectional associations with physical activity and BMI - Alnasser, Sara K.; Shaikh, Narmeen; Alhusseini, Noara (International Journal Of Community Medicine And Public Health, 2026)
Background: Prolonged screen time in the modern digital society, including television viewing, smartphone use, computer use, and video gaming, has emerged as a significant public health concern. Excessive screen exposure may reduce physical activity levels and contribute to obesity. This study aimed to evaluate the association between screen time, physical activity, and obesity among adults living in Saudi Arabia. Methods: A cross-sectional online survey was conducted using a 26-item questionnaire assessing screen time behaviors, physical activity (Godin–Shephard Leisure-Time Physical Activity Questionnaire), and sociodemographic characteristics. Associations were examined using chi-square tests, and multivariable logistic regression was used to identify independent predictors of prolonged weekday computer and smartphone use. Analyses were performed in SPSS version 29 with a two-sided significance level of p<0.05. Results: A total of 1,282 participants completed the survey; 58% were female, and 57% were aged between 20 and 49 years. Overall, 36% of respondents were overweight, 27% were obese, and 64% were physically active. Screen time exceeding four hours per weekday was reported by 26% for television, 39% for computers, 7% for video games, and 67% for smartphones. Several demographic and socioeconomic factors were associated with increased computer and smartphone use. Smartphone use was significantly associated with insufficient physical activity or sedentary behavior, but not with overweight or obesity. Conclusions: High levels of screen time were observed among adults in Saudi Arabia. While prolonged screen exposure was not associated with obesity, excessive screen time, particularly smartphone use, was significantly associated with lower physical activity levels. These findings highlight the need for public health strategies that promote physical activity and address excessive screen use among adults.